Dynamic tuning of terahertz atomic lattice vibration via cross-scale mode coupling to nanomechanical resonance in WSe2 membranes - Bo Xu; Zejuan Zhang; Jiaze Qin; Jiaqi Wu; Luming Wang; Jiankai Zhu; Chenyin Jiao; Wanli Zhang; Juan Xia; Zenghui Wang (Microsystems & Nanoengineering)
Abstract Nanoelectromechanical systems (NEMS) based on atomically-thin tungsten diselenide (WSe2), benefiting from the excellent material properties and the mechanical degree of freedom, offer an ideal platform for studying and exploiting dynamic strain engineering and cross-scale vibration coupling in two-dimensional (2D) crystals. However, such opportunity has remained largely unexplored for WSe2 NEMS, impeding exploration of exquisite physical processes and realization of novel device functions. Here, we demonstrate dynamic coupling between atomic lattice vibration and nanomechanical resonances in few-layer WSe2 NEMS. Using a custom-built setup capable of simultaneously detecting Raman and motional signals, we accomplish cross-scale mode coupling between the THz crystal phonon and MHz structural vibration, achieving GHz frequency tuning in the atomic lattice modes with a dynamic gauge factor of 61.9, the best among all 2D crystals reported to date. Our findings show that such 2D NEMS offer great promises for exploring cross-scale physics in atomically-thin semiconductors.